Synthesis, Radiosynthesis and Biological Evaluation of Buprenorphine‐Derived Phenylazocarboxamides as Novel μ‐Opioid Receptor Ligands. (2nd June 2020) - Krüll, Jasmin; Fehler, Stefanie K.; Hofmann, Laura; Nebel, Natascha; Maschauer, Simone; Prante, Olaf; Gmeiner, Peter; Lanig, Harald; Hübner, Harald; Heinrich, Markus R.
Abstract: Targeted structural modifications have led to a novel type of buprenorphine‐derived opioid receptor ligand displaying an improved selectivity profile for the μ‐OR subtype. On this basis, it is shown that phenylazocarboxamides may serve as useful bioisosteric replacements for the widely occurring cinnamide units, without loss of OR binding affinity or subtype selectivity. This study further includes functional experiments pointing to weak partial agonist properties of the novel μ‐OR ligands, as well as docking and metabolism experiments. Finally, the unique bifunctional character of phenylazocarboxylates, herein serving as precursors for the azocarboxamide subunit, was exploited to demonstrate the accessibility of an 18 F‐fluorinated analogue. Abstract : Targeted replacement of a cinnamide for a phenylazocarboxamide moiety led to a novel type of buprenorphine‐derived opioid receptor ligand that display selectivity for the μ‐subtype. Besides good metabolic stability and no detectable cytotoxicity, the phenylazocarboxamide unit enabled straightforward access to an 18 F‐fluorinated analogue, thus making this substructure a promising building block for future research in medicinal chemistry.